Pemantauan Dinamika Kekeringan Dengan Metode Indeks Vegetasi Berbasis Citra Multispektral Di Kawasan Pertanian Kabupaten Lombok Tengah - Rasyid Ridha; Agus Kurniawan; Febrita Susanti; Ridho Ario Nugroh (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Agriculture contributes 13% to Indonesia's national GDP and supports the livelihoods of 30 million people. In Central Lombok Regency, with 57,355.19 ha of rice fields, the agricultural contribution declined from 26.18% to 25.07% of the GRDP in 2022. This study aims to analyze the dynamics and spatial distribution of drought in Central Lombok's agricultural areas through the use of vegetation indices derived from Landsat multispectral imagery. The methodology includes calculation of the Normalized Difference Vegetation Index (NDVI), Vegetation Condition Index (VCI), Land Surface Temperature (LST), Temperature Condition Index (TCI), and Vegetation Health Index (VHI), validated with rainfall data and spatially analyzed through overlay with rice field type maps. Results indicate extreme drought covering 1,170.56 ha, severe drought 8,375.51 ha, and moderate drought 34,459.80 ha based on VHI analysis. Rainfed rice fields were found to be the most vulnerable, with extreme drought affecting 370.93 ha, severe drought 2,668.35 ha, and moderate drought 11,210.25 ha, while irrigated rice fields were more resilient, dominating the non-drought category with 38,255.27 ha. These findings provide a basis for developing drought vulnerability maps, mitigation planning, and irrigation management to enhance agricultural resilience in Central Lombok Regency.